Testing effects on hardness of a Zr-based metallic glass under nanoindentation. (September 2017) - Li, M.C.; Jiang, M.Q.; Jiang, F.; He, L.; Sun, J.
Abstract: A series of nanoindentation tests were performed on a Zr-based bulk metallic glass at different peak-loads and strain rates. It is observed that the strain rate sensitivity index gradually decreases from positive to almost zero with increasing peak-load. Furthermore, at a fixed strain rate, the indentation hardness firstly shows a dramatic reduction and then becomes stable with increasing peak-load. These observations can be well understood in the framework of the activation and the accumulation of free volume via shear transformation zones. The current work may provide a practical way to tailor the hardness of the metallic glass. Graphical abstract: A positive dependence of hardness on the equivalent strain rate is found. Meanwhile, both the strain rate sensitivity index and the indentation hardness firstly decrease and then become stable with the increasing peak load.